2020
DOI: 10.3390/ijms21030857
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Zerumbone on Colonic Tumorigenesis in Enterotoxigenic Bacteroides fragilis (ETBF)-Colonized AOM/DSS BALB/c Mice

Abstract: Chronic inflammation has been linked to colitis-associated colorectal cancer in humans. The human symbiont enterotoxigenic Bacteroides fragilis (ETBF), a pro-carcinogenic bacterium, has the potential to initiate and/or promote colorectal cancer. Antibiotic treatment of ETBF has shown promise in decreasing colonic polyp formation in murine models of colon cancer. However, there are no reported natural products that have shown efficacy in decreasing polyp burden. In this study, we investigated the chemopreventiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 32 publications
1
16
0
Order By: Relevance
“…Thirty in vivo mouse studies were identified and included in the analysis [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] . 87% of these studies used the C57BL6 mouse strain (26 studies [38 , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [51] , [52] , [53] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] ), 10% used the BALB/c mouse strain (3 studies [54] , [55] , [56] ), and 3% used a germ free (GF) NIH mouse strain (...…”
Section: Resultsmentioning
confidence: 99%
“…Thirty in vivo mouse studies were identified and included in the analysis [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] . 87% of these studies used the C57BL6 mouse strain (26 studies [38 , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [51] , [52] , [53] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] ), 10% used the BALB/c mouse strain (3 studies [54] , [55] , [56] ), and 3% used a germ free (GF) NIH mouse strain (...…”
Section: Resultsmentioning
confidence: 99%
“…The establishment of an AOM/DSSinduced animal model of colon cancer is simple and economical and has a high success rate. [17][18][19] This model can accurately replicate the characteristics of human colon cancer disease. This experiment required 13 weeks to establish a mouse model of colon cancer.…”
Section: Discussionmentioning
confidence: 97%
“…Berberine blocked the secretion of mucosal immune factors, IL-21, IL-22, IL-31, and CD40L in mice, and prevented changes in F. nucleatum -induced intracellular signaling pathways 120 . In another example, zerumbone, the main component of Zingiber zerumbet , has been reported to have antibacterial, antiinflammatory and antitumor activities, and has been shown to reduce ETBF-induced, intestinal inflammation-related CRC by altering the IL-17, β-catenin, Stat3, and NF-κB pathways 121 .…”
Section: Advances In Drug Research For Specific Intestinal Bacteriamentioning
confidence: 99%